Elastic distortions of carbon nanotubes induced by chiral fullerene chains. - Warner, J; Wilson, M (2010)
We show that when Y@C82 metallofullerenes are inserted into single-walled carbon nanotubes (SWNTs) with large diameters of 2 nm, the minimum energy configuration is a double-helix chiral structure extending over hundreds of nanometers. We demonstrate rotation of the double-helix fullerene chain within the nanotube host that induces real time elastic distortions of the nanotube in a crank-shaft manner. Molecular dynamics simulations, employing an atomic description of the confining SWNT and a reduced description of Y@C82, reproduce the key experimental observations.